Effect of Hurricane Maria on HPV, Tdap, and meningococcal conjugate vaccination rates in Puerto Rico, 2015-2019 - Vivian Colón-López; Olga L. Díaz-Miranda; Diana T. Medina-Laabes; Roxana Soto-Abreu; Idamaris Vega-Jimenez; Ana P. Ortiz; Erick L. Suárez (Taylor & Francis Group, 2021)
In September 2017, Hurricane Maria devastated the Caribbean region, among them the US territory of Puerto Rico (PR). Vaccination distribution and uptake suffered from the impact. This study evaluated the trends in monthly vaccination initiation rates for human papilloma virus (HPV), Tdap and meningococcal conjugate (MenACWY) adolescent vaccines from 2015 to 2019, during which it was possible to observe and analyze the impact of Hurricane Maria on vaccine initiation. Monthly initiation rates were estimated. Age-standardized initiation rate ratio (SRR) and 95% CI were estimated. The analysis included 85,340 adolescents; 52.3% were male, and 47.7% were females. September 2017 showed HPV vaccine initiation had the lower rates of all the studied vaccines, with a rate of 75% after the disaster (from a rate of almost 90% in July 2017). Tdap and MenACWY vaccines rates remained above 90% in the same period. The SRR of HPV vaccine for September and October 2017 showed an estimated reduction of 5% and 8% in vaccine initiation rates, respectively for each month, when 2016 was the reference year (p > .05). The SRR of Tdap and MenACWY vaccines for November 2017 showed significant reductions when 2015 and 2016 were reference years (p < .05). HPV vaccine initiation rate was the most severely affected by the Hurricane Maria. Post-natural disaster protocols should strengthen existing programs for facilitate immunization access.